Educación para el amor: una necesidad impostergable - Steele Zúñiga, Gerardo A. (2001)
This article acknowledges the effort done in the field of sexual education by several public entities in Costa Rica. It points out that the accomplishments of the plan implemented so far have not been those expected due to the lack of coordination among the institutions and the people concerned about the importance of sexual education. The author proposes as an option to strongly work in the implementation of a love education strategy, which would have as the backbone of sexuality and sex education, the ethical and philosophical principles of love.